Green Fodder Resources for commercial rabbit farming - Meena, L R; Prasad, Kamta (Indian Farming, 2016)
Angora rabbit can be reared in temperate and sub temperate regions of the country such as Jammu and Kashmir, Himachal Pradesh, hills of Uttar Pradesh, Uttarakhand, West Bengal,Sikkim, North eastern states and hills of Karnataka, Tamil Nadu and Kerala. There are various crops and trees available in the rural areas for successful rearing of rabbit in India.